Overcoming resistant cancerous tumors through combined photodynamic and immunotherapy (photoimmunotherapy) - Kah, Glory; Abrahamse, Heidi (Frontiers in Immunology, 2025)
Cancer is a major health problem as it causes significant mortality globally. In the last decades, conventional and recent therapeutic approaches have been used in oncology for cancer treatment. Despite this, the complete eradication of cancer is challenging, as the existing therapeutic strategies for cancer are typically faced with limitations. This is linked to cancer resistance to treatment, which arises because of the versatile nature of cancerous cells. Novel anticancer therapeutic procedures based on immune system activation, such as photodynamic therapy (PDT) and immunotherapy (IOT), are promising in treating resistant tumors. PDT is a minimally invasive treatment that induces cellular reactive oxygen species (ROS) production for direct elimination of cancerous cells, but can also trigger anticancer effects by activating the immune system of the host. IOT also has significant anticancer efficacy and has emerged as an advanced anticancer treatment that mainly enhances and stimulates the innate immune system of the body to identify and destroy cancerous cells. IOT can also instigate a long-lasting anticancer response by harnessing the body’s immune system. PDT and IOT, when used alone, cannot tackle the issue of cancer resistance. This review elucidates the principles, benefits, and setbacks of PDT and IOT, along with the unique attributes that render them suitable for cancer combination therapy. It underscores the advancement of cancer PDT when utilized in combination with IOT (photoimmunotherapy), while also encapsulating the preclinical evidence regarding the efficacy of photoimmunotherapy, and its combination with nanotechnology (Nano-photoimmunotherapy). The key findings indicate that photoimmunotherapy preclinical methods hold great promise in cancer treatment, as they can directly destroy cancer cells through PDT while also stimulating an increased anticancer immunity through co-delivery of IOT agents. Target-specific moieties can be used in nanotechnology-based anticancer photoimmunotherapy techniques to get past resistance and other therapeutic obstacles. However, clinical utilization of photoimmunotherapy procedures is greatly required to warrant the full efficacy.